Anthropology and the Dialectic of Enlightenment: A Discourse on the Definition and Ideals of a Threatened Discipline - Kapferer, Bruce (The Australian journal of anthropology, 2007)
The knowledge practices of social and cultural anthropology can be conceived as undergoing constant methodological reconsideration or reformulation as a consequence of internal critique and of institutional change effected in the larger educational and political environment. Neo-liberal shifts affecting the institutional context may have influenced a deepening of the crisis in anthropology where the nature of its project has become less certain or has threatened a reconfiguration of such proportion that anthropology may be losing sight of its direction. This essay explores some of the Enlightenment roots of social and cultural anthropology. It is presented as very much an idea that embodies and reflects what Adorno and Horkheimer discussed as the dialectic of Enlightenment. The argument presented is less pessimistic claiming that the distinction of anthropology is in its pursuit of Enlightenment ideals that it has maintained and rehoned as a consequence of its own routine internal critique. The vital implication of the discussion is that anthropology is in a situation of serious threat in largely a post-Enlightenment world. In such a context, the methodological ideals that emerged as integral to the spirit of anthropology are well worth maintaining rather than abandoning. The ideals that are addressed are conceived to be integral to the importance of anthropology as critique and as a knowledge practice capable of sustaining a profound contribution to the understanding of the potential that is human being.